A indignidade sucessória no direito romano : reflexos no direito português = Unworthiness to succeed in roman law : its impact in portuguese law - Justo, António dos Santos (2018)
Equitable barriers to succession were not a unitary element in the law of Rome in antiquity. Unconscionable behaviour by the successor towards the deceased (or family members) were considered by the imperial laws (constitutiones) a factor in succession rights. There has been no shortage of attempts by Romanists to classify these factors into several categories. In this juridical regime, it should be noticed that such conduct does not entail disinheritance; It only precludes retaining inherited goods that passed to the state treasury (the aerarium and later, the fiscus) and, exceptionally, to the persons legally considered. Therefore, equitable barriers to succession were not absolute bars. The Roman state did not immediately acquire the goods, but had to bring an action to determine whether the facts attributed to the putative successor had been established and, if so, declare him barred. The defendant was permitted to defend himself, contesting the action and appealing against the adverse judgment. In Roman law, the list of acts that could result in preclusion were considered to be exhaustive, a this was also later the case in Portuguese law, a situation provoking the disagreement between those who who refuse their extension to similar behaviour, - admitting only analogia legis - and those who admit the analogia iuris, the only kind of analogy that contemporary, non-positivist methodology considers. Another situation that divides Portuguese doctrine has to do with the necessity or not of an action and what its nature is. Considering that the security of legal commerce and the defence of the dignity of the successor requires an action, it seems that this is a declaratory action of simple appreciation: the judge merely tries whether the defendant is the author of the behaviour of which he is accused and, if such is established, declares such conduct wrongful. Equitable has a general character and therefore applies to all kinds of succession, even legitimacy. In this case, as the person precluded from succession is associated with his wrongdoing for all legal purposes (article 2166, paragraph 2 of the Portuguese Civil Code), the latter may provide grounds for disinheritance which, in turn, may also be reflected in the remaining forms of succession. Finally, the possibility that the author of the succession may rehabilitate the person barred from inheritance is not excluded, regard being had to the aforesaid association of preclusion with the wrongdoing in question.